Accuracy of Bone Height and Thickness Measurements in Cone Beam Computed Tomography in the Presence of Porcelain Fused to Metal (PFM) Crowns - Atefeh Gholampour; Melika Mollaei; Mona Alimohammadi; Sara Yaghoubi; Abolfazl Hosseinnataj; Zahra Mollazadeh (Journal of Indian Academy of Oral Medicine and Radiology)
Background: Cone beam computed tomography (CBCT) is a valuable imaging modality in dentistry and has a remarkable role in the analysis of the hard tissue of the maxillofacial region. However, the artifact caused by crowns and some other dental interventions reduces its quality and creates problems in the interpretation of the images. Therefore, this research aims to investigate the accuracy of CBCT linear measurement in the presence of porcelain fused to metal (PFM) restorations. Materials and Methods: In this experimental study, 12 sheep mandibles were used. Radiopaque markers (gutta-percha) were located on the buccal and lingual ridges, and the height and thickness of the bone were measured using a digital caliper (direct measurement). Subsequently, the samples were scanned in three steps with the CBCT device: The first scan was performed without placing the crown (the base image), the second scan was performed with one PFM crown, and the third scan was performed in the presence of three side-by-side crowns. The data were analyzed using SPSS software V.22. The significance level was considered 0.05. Findings: There was no significant difference between the direct measurement and the baseline image in the measurement of bone height and thickness. Moreover, increasing the number of crowns did not affect the accuracy of CBCT scans. Conclusion: According to the findings of this study, the presence of metal-ceramic crowns did not reduce the accuracy in the linear measurement of alveolar bone height and thickness.